Lack of association between genetic variants in the 19q13.32 region and CHD risk in the Algerian population: a population-based nested case-control study - Boulenouar, Houssam (Afr Health Sci, 2020)
BACKGROUND: Coronary Heart Disease (CHD) is a major cause of morbidity and mortality over the world; intermediate traits associated with CHD commonly studied can be influenced by a combination of genetic and environmental factors. OBJECTIVE: We found previously significant association between three genetic polymorphisms, and the lipid profile variations in the Algerian population. Considering these findings, we therefore decided to assess the relationships between these polymorphisms and CHD risk, METHODS: We performed a population-based, cross-sectional study, of 787 individuals recruited in the city of Oran, in which, a nested case-control study for MetS, T2D, HBP, obesity and CHD were performed. Subjects were genotyped for four SNP rs7412, rs429358 rs4420638 and rs439401 located in the 19q13.32 region. RESULTS: The T allele of rs439401 confers a high risk of hypertension with an odds ratio (OR) of 1.46 (95% CI [1.12-1.9], p = 0.006) and the G allele of rs4420638 was significantly associated with a decreased risk of obesity, OR 0.48 (95% CI [0.29-0.81], p = 0.004). No associations were found for MetS, T2D and CHD. CONCLUSION: Although the studied genetic variants were not associated with the risk of CHD, the 19q13.32 locus was associated with some of the cardiometabolic disorders in Algerian subjects.